Retracted: VR Technology in Marketing From the Perspective of Customer Experience - Xiangxi Kong; Dewen Liu; Liangyu Min (IEEE Access)
Virtual reality technology is a new media technology. On the one hand, virtual reality technology has brought a brand-new impact on people’s production and life. On the other hand, our understanding of virtual reality is far from enough, and its derived social problems, Academic issues and ethical issues need to be further explored, and use correct theories to promote and guide the further development of technology. In the process of market segmentation being considered as the core concept of marketing strategy, many scholars at home and abroad have conducted a lot of research on market segmentation. Based on the research results at home and abroad, this article uses factor analysis, cluster analysis, comparative analysis, and inductive deduction as research methods to establish an analysis model for the application of VR technology in marketing from the perspective of customer experience. Based on the application of VR technology in marketing from the perspective of customer experience, the research results show that after using the research method of this article, the data error rate is significantly controlled, and the data error rate is maintained within five percentage points, compared with previous studies The method data accuracy rate is increased by 15%, and the data accuracy rate is higher, which has certain practical value.